An efficient convolutional neural network-based diagnosis system for citrus fruit diseases - Huang, Zhangcai; Jiang, Xiaoxiao; Huang, Shaodong; Qin, Sheng; Yang, Su (Frontiers in Genetics, 2023)
Fruit diseases have a serious impact on fruit production, causing a significant drop in economic returns from agricultural products. Due to its excellent performance, deep learning is widely used for disease identification and severity diagnosis of crops. This paper focuses on leveraging the high-latitude feature extraction capability of deep convolutional neural networks to improve classification performance. In detail, the proposed network is formed by combining the Inception module with the current state-ofthe-art EfficientNetV2 for better disease identification of citrus fruits. Compared to existing networks, the proposed method achieved recognition accuracy of over 95%. In addition, comparing the accuracy of the segmentation models. VGG-U-Net, a network generated by replacing the backbone of U-Net with VGG, is found to have the best segmentation performance with an accuracy of 87.66%. This method is most suitable for diagnosing the severity level of citrus fruit diseases. In addition, transfer learning is applied to improve the training cycle of the network model, both in the detection and severity diagnosis phases of the disease. The results of the comparison experiments revealed that the proposed method is effective in identifying and diagnosing the severity of citrus fruit diseases.